2015
DOI: 10.1093/jjco/hyv175
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment neutrophil-to-lymphocyte ratio predicts prognosis in patients with locoregionally advanced laryngeal carcinoma treated with chemoradiotherapy

Abstract: Objective: The aim of this study was to investigate the effect of neutrophil-to-lymphocyte ratio on the prognosis of patients with locoregionally advanced laryngeal carcinoma treated with chemoradiotherapy. Methods: One hundred and twenty-five patients with locoregionally advanced laryngeal carcinoma (cT3-4 N0-3M0) treated with chemoradiotherapy were reviewed retrospectively. Chemoradiotherapy comprised external beam radiotherapy to the larynx (70 Gy) with three cycles of cisplatin at 3 week intervals. The sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…Finally, 25 studies with 28 cohorts fulfilled the criteria and were eligible in this meta‐analysis. All of them are retrospective observation studies.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 25 studies with 28 cohorts fulfilled the criteria and were eligible in this meta‐analysis. All of them are retrospective observation studies.…”
Section: Resultsmentioning
confidence: 99%
“…The full texts of 36 studies were then inspected. After excluding studies according to the exclusion criteria, 19 studies enrolling 3770 patients were included in the present study (see Table ) . Cohen's kappa for inter‐reviewer agreement was 0.88.…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA flow chart of the systematic review can be found in Figure . An initial search done using the search strategy (Supporting Materials) obtained an initial 900 results.…”
Section: Methodsmentioning
confidence: 99%